Divertor studies in nitrogen induced completely detached H-modes in full tungsten ASDEX Upgrade. (6th February 2015) - Reimold, F.; Wischmeier, M.; Bernert, M.; Potzel, S.; Kallenbach, A.; Müller, H.W.; Sieglin, B.; Stroth, U.
Abstract: The first stable completely detached H-mode plasma in the full tungsten ASDEX Upgrade has been achieved. Complete detachment of both targets is induced by nitrogen seeding into the divertor. Two new phases are added to the detachment classification described in Potzel et al (2014 Nucl. Fusion 54 013001 ): first, the line integrated density increases by about 15% with partial detachment of the outer divertor. Second, complete detachment of both targets is correlated to the appearance of intense, strongly localized, stable radiation at the X-point. Radiated power fractions, f rad, increase from about 50% to 85% with nitrogen seeding. X-point radiation is accompanied by a loss of pedestal top plasma pressure of about 60%. However, the core pressure at ρ pol  < 0.7 changes only by about 10%. H 98  = 0.8–1.0 is observed during detached operation. With nitrogen seeding the edge-localized mode (ELM) frequency increases from the 100 Hz range to a broadband distribution at 1–2 kHz with a large reduction in ELM size.